Expression of tomato salicylic acid (SA)‐responsive pathogenesis‐related genes in Mi‐1‐mediated and SA‐induced resistance to root‐knot nematodes. (5th December 2013) - Molinari, Sergio; Fanelli, Elena; Leonetti, Paola
Summary The expression pattern of pathogenesis‐related genes PR‐1, PR‐2 and PR‐5, considered as markers for salicylic acid (SA)‐dependent systemic acquired resistance (SAR), was examined in the roots and shoots of tomato plants pre‐treated with SA and subsequently infected with root‐knot nematodes (RKNs) (Meloidogyne incognita). PR‐1 was up‐regulated in both roots and shoots of SA‐treated plants, whereas the expression of PR‐5 was enhanced only in roots. The over‐expression of PR‐1 in the whole plant occurred as soon as 1 day after SA treatment. Up‐regulation of the PR‐1 gene was considered to be the main marker of SAR elicitation. One day after treatment, plants were inoculated with active juveniles (J2s) of M. incognita. The number of J2s that entered the roots and started to develop was significantly lower in SA‐treated than in untreated plants at 5 and 15 days after inoculation. The expression pattern of PR‐1, PR‐2 and PR‐5 was also examined in the roots and shoots of susceptible and Mi‐1‐carrying resistant tomato plants infected by RKNs. Nematode infection produced a down‐regulation of PR genes in both roots and shoots of SA‐treated and untreated plants, and in roots of Mi‐carrying resistant plants. Moreover, in resistant infected plants, PR gene expression, in particular PR‐1 gene expression, was highly induced in shoots. Thus, nematode infection was demonstrated to elicit SAR in shoots of resistant plants. The data presented in this study show that the repression of host defence SA signalling is associated with the successful development of RKNs, and that SA exogenously added as a soil drench is able to trigger a SAR‐like response to RKNs in tomato.